Review of Smith, K.L., & Dickson, K.A. (Eds.).(2016).Open access and the future of scholarly communication: Policy and infrastructure. NY: Rowan and Littlefield. - Donna Church (Journal of New Librarianship, 2017)
Review of Smith, K.L., & Dickson, K.A. (Eds.). (2016). Open access and the future of scholarly communication: Policy and infrastructure. NY: Rowan and Littlefield